ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN TERKOMPUTERISASI PADA PT PD (KANTOR PUSAT) - MAGDALENA EKA NOVENA (Universitas Katolik Widya Mandala Surabaya, 2012)
The existing payroll system on PT PD less accordance with the current development. First, the employee attendance system still using check clock machine. This is vulnerable to fraud that could be done by employees and then calculating the working days using manual method, so sometimes errors are made in the calculation. Furthermore, PT PD doesn’t have employee database, whereas it takes quite a lot of data and the number of employees are quite a lot so to manage and maintenance the data becomes a little difficult. With these problems, it is necessary to repair and design a better system so that the problems faced by companies can be somewhat resolved. In thus research there were seven techniques in the process of data analysis, that is analyze the company’s payroll system and procedures, designing flowcharts and data flow diagram for company’s payroll system also develop the existing system, create an entity relation diagram, create a database of employee, create a payroll system interface, improve the related document payroll system that still has shortcomings and create a limit access to the payroll system. With the design of a computerized payroll system expected to reduce calculation errors on employee attendance, employee’s salary can be given on time and with the correct amount and maintenance of employee data can be done on a regular basis.